Efficacy and safety of immune checkpoint inhibitors for advanced squamous non-small cell lung cancer: a systematic review and network meta-analysis - Liu, Na; Zhang, Baowanze; He, Jiali; Li, Su (Frontiers in Immunology, 2025)
ObjectiveSignificant efficacy heterogeneity exists between first- and second-line immunotherapy regimens for advanced squamous non-small cell lung cancer (SqNSCLC), but most regimens lack directly comparable clinical trial evidence, resulting in unclear prioritization. This analysis identifies optimal treatment strategies by evaluating differences in efficacy across immune checkpoint inhibitors (ICIs).MethodsWe search through comprehensive databases, including PubMed, Embase, the Cochrane Library and the Clinical Trials Database. Traditional meta-analysis was done using Stata 15.0, while Bayesian-framework network meta-analysis was implemented with R’s GEMTC package via Markov chain Monte Carlo simulation. Subgroup analyses were performed for different PD-L1 expression levels, number of treatments, ethnic groups, and smoking history.ResultsWe included 25 randomized controlled trials. Immune-related therapy can provide significant benefit relative to chemotherapy alone in advanced SqNSCLC. Compared with chemotherapy, except for ipilimumab+chemo [HR = 0.92,95%CI: (0.59-1.40)], atezolizumab+chemo [HR = 0.88, 95%CI: (0.56-1.40)], and durvalumab+chemo [HR = 0.84, 95% CI: (0.52-1.40)], durvalumab+ tremelimumab+chemo [HR = 0. 88, 95% CI: (0.54-1.40)], which significantly improved overall survival(OS). Cemiplimab [HR = 0.48, 95% CI: (0.34-0.67)] showed the best OS benefit. Compared with chemotherapy, all immunotherapies significantly improved progression-free survival (PFS) except for ipilimumab+chemo [HR = 0.87, 95% CI: (0.75-1.00)]. Sugemalimab+chemo provided the best survival benefit [HR = 0.34, 95% CI: (0.24-0.48)]. For PD-L1≥50% tumors, penpulimab showed excellent OS and PFS; for PD-L1 1-49% tumors, pembrolizumab+chemo and camrelizumab+chemo achieved the best OS and PFS, respectively; for PD-L1≥1% tumors, the tislelizumab+chemo and camrelizumab+chemo showed the best OS and PFS results, while for tumors with PD-L1 <1%, both nivolumab and serplulimab+chemo provided significant survival benefit. In Asian patients, patients treated with pembrolizumab or pembrolizumab + chemotherapy had favorable OS and PFS benefits. In non-Asian patients, there was also favorable OS and PFS benefit with cemiplimab. For former/current smokers, pembrolizumab+chemotherapy and camrelizumab+chemotherapy had significant OS and PFS benefit, but most immunotherapies did not improve OS and PFS in never smokers. Camrelizumab+chemo [OR = 3.5, 95% CI: (2.3-5.3)] had the best overall response rate (ORR) benefit. Ipilimumab+chemo had the highest incidence of adverse events (AEs) [OR = 2.0, 95% CI:(1.5-2.7)].Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251027447.